Healthcare bias and health inequalities towards displaced Syrians in Lebanon: a qualitative study - Khalifeh, Riwa; D’Hoore, William; Saliba, Christiane; Salameh, Pascale; Dauvrin, Marie (Frontiers in Public Health, 2023)
This is a provisional file, not the final typeset articleThe findings indicated that there were barriers to accessing healthcare related to the SDOH, such as transportation and financial resources. The results also suggested that DS perceived health biases, including discriminatory behavior from Lebanese healthcare providers, stereotypes and racism leading to health inequalities.Based on the perceptions and experiences reported by participants, the underlying causes of biases are due to the fragility of the Lebanese healthcare system when facing a humanitarian crisis as well as a collapsing infrastructure torn by past wars and the current socio-political and financial crises in the country. Global initiatives are required to provide the necessary resources needed for offering equitable health services. Such initiatives involve addressing biases, health inequities, discrimination, and the lack of a Lebanese infrastructure system for the provision of healthcare. Addressing health inequalities remains a major health objective in achieving health equity on the micro level (cultural awareness and competencies) and macro level (equitable distribution of resources, implementation of a universal health coverage) in order to guarantee quality healthcare services to DS.